Boron neutron capture therapy for vulvar melanoma and genital extramammary Paget's disease with curative responses - Hiratsuka, Junichi; Kamitani, Nobuhiko; Tanaka, Ryo; Yoden, Eisaku; Tokiya, Ryuji; Suzuki, Minoru; Barth, Rolf F.; Ono, Koji (Cancer communications (London, England), 2018)
Background Although the most commonly recommended treatment for melanoma and extramammary Paget's disease (EMPD) of the genital region is wide surgical excision of the lesion, the procedure is highly invasive and can lead to functional and sexual problems. Alternative treatments have been used for local control when wide local excision was not feasible. Here, we describe four patients with genital malignancies who were treated with boron neutron capture therapy (BNCT). Methods The four patients included one patient with vulvar melanoma (VM) and three with genital EMPD. They underwent BNCT at the Kyoto University Research Reactor between 2005 and 2014 using para‐boronophenylalanine as the boron delivery agent. They were irradiated with an epithermal neutron beam between the curative tumor dose and the tolerable skin/mucosal doses. Results All patients showed similar tumor and normal tissue responses following BNCT and achieved complete responses within 6 months. The most severe normal tissue response was moderate skin erosion during the first 2 months, which diminished gradually thereafter. Dysuria or contact pain persisted for 2 months and resolved completely by 4 months. Conclusions Treating VM and EMPD with BNCT resulted in complete local tumor control. Based on our clinical experience, we conclude that BNCT is a promising treatment for primary VM and EMPD of the genital region. Trial registration numbers UMIN000005124